L'Interdiction, or, Balzac on the margins of law and realism - Counter, A (Routledge, 2017)
Honoré de Balzac’s 1836 novella L'Interdiction is the story of a wife's attempt to have her husband declared legally incompetent by reason of insanity, and of an idealistic juge d'instruction's investigation of her request. In a procedurally detailed recounting of the investigation, Balzac reflects on the law's role alongside other discourses of authority in defining and adjudicating normal and abnormal behaviour. The eventual discovery that the husband is sane and that the wife's motives in claiming the contrary are grossly self-interested leads the narrator to familiar Balzacian conclusions about the marginalization of virtue – its depiction, indeed, as a form of madness – in a corrupt modern society. Yet the text's constant evocation of questions of plausibility, verisimilitude and realism draws these legal considerations into a self-reflexive dispute about narrative aesthetics, a mise-en-abyme of contemporaneous debates between the literary approach known as ‘idealism’, and Balzac's own nascent conception of the novelist's art, which would one day be known as ‘realism’. Despite its superficial moralizing, the text leads inexorably to the conclusion that idealism – the judge's, the husband's, Balzac's contemporary novelists' – is, simply, impossible, and must always yield to the demands of reality. The novella thus reveals how literature not only engages with legal issues and arguments, but appropriates them for the purposes of intra-literary aesthetic debates about how best to represent the world. Indeed, L'Interdiction gives a sense of how legal and representational disputes can in fact be two aspects of the same fundamental quarrel.